The Effect of the Numbered Head Together (NHT) Learning Model and The Use of The Kahoot Interactive Application on Student Learning Outcomes in The Citizenship Education Subject In Grade XI - Rutmita, Elmi; Ambarita, Prini D.; Banjarnahor, Daulat Nathanael (Jurnal Ilmu Sosial dan Humaniora, 2025)
The research problem addressed in this study is: (1) What is the effect of the Numbered Head Together (NHT) learning model and the use of the interactive Kahoot application on students' learning outcomes in Civic Education for Grade XI students at SMA Negeri 2 Pematangsiantar in the 2025/2026 academic year?The objective of this study is: (1) To determine the effect of the Numbered Head Together (NHT) learning model and the use of the interactive Kahoot application on students' learning outcomes in Civic Education for Grade XI students at SMA Negeri 2 Pematangsiantar in the 2025/2026 academic year.This study uses a quantitative approach with a quasi-experimental pretest-posttest design. The population consists of all Grade XI students at SMA Negeri 2 Pematangsiantar, totaling 358 students. The sample consists of two classes: class XI-2 and XI-6, each with 36 students, resulting in a total sample of 72 students. The research instrument used is a multiple-choice test.The posttest results in the control class show a minimum score of 50, a maximum score of 75, and an average score of 63.33. In the experimental class, the minimum posttest score is 65, the maximum is 90, and the average score is 80.83. The comparison of learning outcome categories shows that the experimental class has a higher frequency of better scores, with an average of 80.83, minimum 65, and maximum 90.The t-test results indicate that the calculated t-value (t_count) is 8.490, while the critical t-value (t_table) is 0.329, with a Sig. (2-tailed) value of 0.000 < 0.05.Based on hypothesis testing using a significance test (t-test), the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. Therefore, the following conclusions are drawn:There is an effect of the Numbered Head Together (NHT) learning model on students' learning outcomes in Civic Education.There is an effect of the use of the Kahoot interactive application on students' learning outcomes in Civic Education.There is a combined effect of the NHT learning model and the Kahoot application on students' learning outcomes in Civic Education for Grade XI students at SMA Negeri 2 Pematangsiantar in the 2025/2026 academic year